THE ROLE OF MATHEMATICS IN EDUCATION AND TECHNOLOGY - Shokirova Farangiz (PEDAGOGS, 2024)
Abstract: This article examines the basic role of mathematics in modern education and technology. It highlights the integration of mathematics in STEM (Science, Technology, Engineering, Mathematics) fields,underscoring its impact on academic success and innovation. By exploring the use of technology in mathematics education, the article demonstrates how digital tools enhance learning outcomes and prepare students for 21st-century challenges.